2013
DOI: 10.3109/09537104.2013.829211
|View full text |Cite
|
Sign up to set email alerts
|

Activated platelet chemiluminescence and presence of CD45+ platelets in patients with acute myocardial infarction

Abstract: It has been found that in 15% of acute myocardial infarction patients' platelets generate reactive oxygen species that can be detected with luminol-enhanced chemiluminescence of platelet-rich plasma within 8-10 days after acute myocardial infarction. This increase in generate reactive oxygen species production coincides with the emergence of CD45(+) platelets. The ability of platelets to carry surface leukocyte antigen implies their participation in exchange of specific proteins in the course of acute myocardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
0
5
0
3
Order By: Relevance
“…They were recently detected in the blood of patients with myocardial infarction. 20 In our recent work, we showed that increased counts of platelets with CD45 leukocyte antigens are characteristic for patients with restenosis in DES. 14 In the present article, we demonstrate that patients with type 2 DM and in-stent restenosis in DES have higher counts of CD45+ platelet in circulation than patients with in-stent restenosis in DES but without type 2 DM (OR: 4.51 vs 2.31, respectively).…”
Section: Discussionmentioning
confidence: 94%
“…They were recently detected in the blood of patients with myocardial infarction. 20 In our recent work, we showed that increased counts of platelets with CD45 leukocyte antigens are characteristic for patients with restenosis in DES. 14 In the present article, we demonstrate that patients with type 2 DM and in-stent restenosis in DES have higher counts of CD45+ platelet in circulation than patients with in-stent restenosis in DES but without type 2 DM (OR: 4.51 vs 2.31, respectively).…”
Section: Discussionmentioning
confidence: 94%
“…The presence of leukocyte membrane antigen (CD45) on platelets is strong evidence for the interaction between these cells. 70,71 Larger platelets tend to be more viscous and easier to aggregate by secreting prothrombotic and vasoactive factors and by expressing high levels of adhesion factors. [72][73][74] Fuster et al 75 showed that postoperative thromboembolism promotes the development of ISR.…”
Section: Parameters Of Platelet Activationmentioning
confidence: 99%
“…В тромбоцитах АФК вырабатываются при активации глутатионовой системы, а также при метаболизме арахидоновой кислоты и фосфоинозитидов. Вырабатываемые тромбоцитами активные формы кислорода могут выполнять роль вторичных мессенджеров и регулировать функцию тромбоцитов [9][10][11]18].…”
Section: Discussionunclassified
“…УЛХТ измеряли в относительных световых единицах (relative light unit -RLU). Более подробное описание этапов проведения измерения ФАТ-стимулированной УЛХТ опубликовано нами ранее [10,11].…”
Section: материал и методыunclassified
See 1 more Smart Citation